Diseño de una propuesta de creación de un clúster agroproductivo en el cantón Portoviejo. - Cedeño Cool, Erika Concepción (2018)
The present thesis aimed to design a proposal for the creation of an agro-productive clúster to strengthen the performance of the primary sector in Portoviejo canton. Therefore, in its development it was necessary to use types of field and bibliographical research; in addition, methods such as deductive, inductive, analytical and statistical; finalizing the methodological part with the survey technique, which allowed to carry out the collection of information pertinent to the study subject. It is worth mentioning that this research was based on the application of three main phases where stages and activities were developed. In the first instance, the collection centers that exist in the Portoviejo canton were identified and quantified, in order to have knowledge of the number of centers that were linked to the sector and thus proceed with the survey application. For this purpose, the data collected in the previous phase was processed by graphically tabulating the results obtained regarding the storage centers, logistics, financial and non-financial entities, productive associations, among others with their respective analysis, using such information as a tool to elaborate the actors comparative matrix already mentioned. Therefore, the participants that will become part of the clúster were classified and selected; for which the key competences were considered according to the selected model. Finalizing, with the design of the agroproductive clúster.